Arctic cinema: from horror through dramas and thrillers To Action movies and fiction (Part II) - I. S. Zonn; И. С. Зонн (The Centre of Regional Research, 2023)
The article examines Arctic thrillers, action films and fantasy films. Presented kaleidoscope of horror, drama, thriller, science fiction and action films, with all its plot differences, is united by almost a single location, the Arctic north. Against his background, all maginable and unimaginable events occur. It enhances or weakens the role of what is happening with its whiteness, making the viewer’s screen even whiter. This is an artistic space in which characters are placed and actions, are performed. The silence of the Arctic is its action. The films reviewed are extremely different, responding to the spirit of the time when they were filmed. Their placement about genres is conditional since they all have a cinematic hybridity. Each tape combines all kinds of genres under consideration. We tried to correlate a number of films with temporary political-social processes. Вторая часть статьи посвящена рассмотрению арктических триллеров, боевиков (экшен фильмов) и фантастических фильмов. Представленный калейдоскоп фильмов – хоррор, драма, триллер, фантастика и боевик при всем своем сюжетном различии объединен практически единой локацией — арктическим севером. На его фоне происходят все мыслимые и не мыслимые события. Он усиливает или ослабляет роль происходящего, своей белизной, делая еще белее зрительский экран. Это художественное пространство, в котором размещаются персонажи и совершаются действия. Молчание Арктики — это ее действие. Рассмотренные фильмы чрезвычайно разные, отвечающие духу времени, когда они снимались. Их размещение по жанрам условно, так как всем им присуща кинематографическая гибридность. Каждая лента сочетает в себе все виды рассматриваемых жанров. Мы постарались ряд фильмов соотнести с временными политико-социальными процессами.